From Manuscript to Printed Book in the Fifteenth Century. Textual and Dialectal Analysis of the Spanish Translation of Salustio by Francisco Vidal de Noya - Fernández Álvarez, María (2022)
This article analyzes the manuscript ANC1-960-T-1219, which contains the Spanish translation of two works by Sallust: The Conspiracy of Catiline and The Jugurthine War. In our research we have determined that the text of the testimony corresponds to a mid-fifteenth century translation by Francisco Vidal de Noya, a person close to the Aragonese court and mentor of King Ferdinand the Catholic. In this study we analyze the manuscript from a graphic, morphosyntactic and lexical point of view, which allows us to investigate the possible linguistic influence of the peninsular east in this historiographic text in Spanish. Furthermore, we will compare some of the analyzed phenomena with the text from the first edition of the translation, printed in Zaragoza in 1493, in order to observe the possible linguistic variants between the manuscript and the printed version.